Literature Review: The Effect of Ajwa Date Consumption on Menstrual Pain Intensity in Women of Reproductive Age - Andi Bayan Zhafirah; Nasruddin Andi Mappaware; Amelia Abdullah (Newinera Publisher, 2025)
Dysmenorrhea is one of the most common menstrual disorders among women of reproductive age, characterized by lower abdominal pain due to increased prostaglandin levels that trigger excessive uterine contractions. Although nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used, their long-term use may cause adverse effects. Therefore, natural and safe alternatives are needed, such as Ajwa dates (Phoenix dactylifera L.), which contain bioactive compounds like flavonoids, phenols, and phytoestrogens that may reduce menstrual pain through hormonal regulation and anti-inflammatory mechanisms. This study aimed to review the effect of Ajwa date consumption on the intensity of menstrual pain in women of reproductive age. This research employed a literature review design with a narrative approach. Data were obtained from five relevant national and international journals that discussed the effects of Ajwa dates on estrogen, progesterone, and inflammatory mechanisms. The collected data were analyzed qualitatively to identify the relationship between variables and summarize the main findings of each study. The review showed that Ajwa dates can increase estrogen and progesterone levels, which help suppress prostaglandin production, relax uterine muscles, and inhibit cyclooxygenase enzymes (COX-1 and COX-2). Additionally, their nutritional content, such as vitamins and minerals, provides a natural analgesic effect that supports physiological balance during menstruation. Consumption of Ajwa dates has the potential to serve as a safe and effective non-pharmacological therapy to reduce menstrual pain intensity through synergistic hormonal, anti-inflammatory, and nutritional mechanisms